2014
DOI: 10.1038/ejcn.2013.275
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of pistachio consumption on glucose and insulin, satiety hormones and endothelial function in the metabolic syndrome

Abstract: Compared with white bread, pistachio consumption reduced postprandial glycemia, increased glucagon-like-peptide levels and may have insulin-sparing properties. These effects could be beneficial for individuals with diabetes and metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
66
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 40 publications
7
66
0
3
Order By: Relevance
“…Randomized clinical trials found that patients consuming a pistachio-supplemented diet show significantly decreased postprandial glycemia, insulin, fasting glucose, and HOMA-IR, and increased GLP-1 [12,13]. Based on these considerations, nuts may potentially improve glycemic control and reduce inflammatory factors in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Randomized clinical trials found that patients consuming a pistachio-supplemented diet show significantly decreased postprandial glycemia, insulin, fasting glucose, and HOMA-IR, and increased GLP-1 [12,13]. Based on these considerations, nuts may potentially improve glycemic control and reduce inflammatory factors in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these considerations, nuts may potentially improve glycemic control and reduce inflammatory factors in diabetic patients. However, there is little evidence for the efficacy of pistachio on glycemic control of diabetic patients [12][13][14]. Therefore, this study was designed to investigate the effectiveness of pistachio consumption on blood glucose of type 2 diabetic patients in a crossover clinical trial.…”
Section: Introductionmentioning
confidence: 99%
“…[76], yemek sonrası glukoz seviyelerini incelediği çalışmasında glisemik indeksi yüksek pirinç ve makarna gibi yaygın karbonhidrat içeren gıdalara antepfıstığını eklemiş ve tüketen kişilerin kan glukoz seviyesinin önemli bir oranda azaldığını tespit etmişlerdir. Ayrıca, antepfıstığı daha uzun süre tokluk hissinin sürdürülmesine ve yemek sonrası kan glikoz konsantrasyonlarının düşürülmesine katkı sağlayan düşük glisemik indekse sahip bir besin maddesidir [77,78]. Düşük glisemik indekse sahip olan antepfıstığı potansiyel olarak diyabet riskini azaltmaktadır [76,77].…”
Section: İnsan Sağliği Açisindan Antepfistiğinin öNemi̇unclassified
“…Ayrıca, antepfıstığı daha uzun süre tokluk hissinin sürdürülmesine ve yemek sonrası kan glikoz konsantrasyonlarının düşürülmesine katkı sağlayan düşük glisemik indekse sahip bir besin maddesidir [77,78]. Düşük glisemik indekse sahip olan antepfıstığı potansiyel olarak diyabet riskini azaltmaktadır [76,77]. Tip 2 diyabete sahip yetişkinlerin diyetinde günlük enerjinin %20'sini antepfıstığından sağlayan grupla diyetinde antepfıstığı bulunmayan (kontrol) grup karşılaştırıldığında daha düşük toplam kolesterol, trigliserid ve fruktozamin tespit edilmiştir.…”
Section: İnsan Sağliği Açisindan Antepfistiğinin öNemi̇unclassified
See 1 more Smart Citation